Optimalisasi Kompetensi Primavista Mahasiswa Instrumen Pokok Piano Melalui Metode Drill - Raden Roro Maha Kalyana Mitta Anggoro (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Every musical instrument that is taken at the college "demands" students to be mastery learning, in both theoretical and practical aspects, as well as possible. However, in the process, there are obstacles that often arise. As in learning the Piano Major course. Based on observations in class, students are constrained in terms of primavista. With the character of the piano score that is consisting of two staves, students are constrained to coordinate their cognitive processing when reading piano scores, with the application of their ten fingers when playing the piano. This study discusses the primavistalearning of piano with the drill method. The type of research conducted was qualitative research, which was conducted in Music Arts Study Program, Universitas Negeri Surabaya.Based on the results, there was a significant improvement in the students' ability to apply the music notation they had read primavistly. In the pre-test session, most of the students' scores were below 40%. However, when the post-test session was conducted, the results of the work shown were very satisfactory. All students were able to achieve scores above 70%. Based on these results, it can be stated that the drill method has succeeded in optimizing the development of primavistaabilities of piano students. It is hoped that this method can be used routinely in piano classes so that students' primavistaabilities can be further honed.